1 2 3 4 (wordless diagrams). - Holmes, Nigel, ....- (New York : Bloomsbury, 2005)
Award-winning illustrator and graphic designer Nigel Holmes depicts the things we do every day like you've never seen them before. Pruning a rose or building a sandcastle might seem like common activities, but when you see them visualized on paper in wordless, step-by-step diagrams, you'll discover them anew. From how to tie a knot in a cherry stem with your tongue to how to make a grilled cheese sandwich, from how to carve a turkey to how to change a nappy, Nigel Holmes's striking diagrams will entertain and educate. Wordless Diagrams will win you over without saying a word.
Keywords: Grafische vormgeving; Vormgeving